Acute Endophthalmitis after Intravitreal Bevacizumab Injections at The Tertiary Centre in Nepal - Pradhan, Eli; Duwal, Sushma; Bajimaya, Sanyam; Thapa, Raba; Sharma, Sanjita; Manandhar, Anu; Poudel, Manish; Paudyal, Govinda (Nepalese Journal of Ophthalmology, 2018)
Introduction: There are many reports of endophthalmitis following Anti- VEG F use in developed countries and from India, but there are none from Nepal yet. Therefore, the aim of this study was to report the prevalence and management of acute endophthalmitis after intravitreal injection of bevacizumab. Methods: This is a clinical, retrospective, non-comparative study, performed in Tilganga Institute of Ophthalmology, Kathmandu, Nepal from Jan 2015 till Dec 2016. All consecutive cases of intravitreal 1.25 mg of bevacizumab injections during the study period were collected from Bevacizumab registry of the operation theatre. A total number of endophthalmitis, following intravitreal bevacizumab injections were collected from Endophthalmitis registry. The statistical analysis was carried out by SPSS for percentage calculation and its 95% Confidence Interval (CI) calculation. Results: There were 4182 injections performed during the study period for various retinal conditions. Two eyes of two patients with acute postoperative endophthalmitis were identified in the first week following intravitreal injections of 1.25 mg bevacizumab among a total of 4128 injections with a prevalence of 0.048% (95% CI: 0.00 to 0.12.). Conclusions: The prevalence of acute endophthalmitis following intravitreal Bevacizumab in our retrospective series was 0.048% and was comparable with the other studies conducted elsewhere. Acute post-injection endophthalmitis following intravitreal bevacizumab can result in severe loss of vision. Therefore prompt recognition and treatment are important part of its management in such patients.